2019
DOI: 10.1111/aas.13367
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous extracorporeal membrane oxygenation treatment in a low‐volume and geographically isolated cardiothoracic centre

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) treatment is generally offered in large tertiary cardiothoracic referral centres. Here we present the indications and outcome of venovenous-ECMO (VV-ECMO) treatment in a low-volume, geographically isolated single-centre in Iceland, a country of 350 000 inhabitants.Our hypothesis was that patient survival in such a centre can be similar to that at high-volume centres. Methods: A retrospective study that included all patients treated with VV-ECMO inIceland f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…6,14,15 In fact, even very low-volume hospitals have revealed short-and long-term outcomes in patients undergoing V-V ECMO comparable to larger centers. 27 So why have we not been able to identify any volumeoutcome relationship? First of all, only two of the mentioned studies analyzing ECLS volume and outcome investigated specifically patients undergoing V-V ECMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,15 In fact, even very low-volume hospitals have revealed short-and long-term outcomes in patients undergoing V-V ECMO comparable to larger centers. 27 So why have we not been able to identify any volumeoutcome relationship? First of all, only two of the mentioned studies analyzing ECLS volume and outcome investigated specifically patients undergoing V-V ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is suggested that hospitals with more experience are rewarded with better results, this has not been demonstrated consistently in the ECLS literature 6,14,15 . In fact, even very low‐volume hospitals have revealed short‐ and long‐term outcomes in patients undergoing V‐V ECMO comparable to larger centers 27 …”
Section: Discussionmentioning
confidence: 99%
“…44,46,48,49,51 However, volume per se might not be the leading factor; several important factors include training, protocols, team expertise, benchmarking, maintaining a low threshold for asking for support. 51,53,68…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the lower mortality reported by low-volume centers supports the importance of timely access to local ECLS. 43,[50][51][52][53][54][55][56] Furthermore, volume per se might not be the leading factor; several important factors include training, protocols, team expertise, benchmarking, and maintaining a low threshold for asking for support. 51,53 Other nations included in GENERATE present a different picture.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it ties in with the concept of human factors, that more ECLS training may be needed low volume center to have better the clinical outcomes. 49 , 50 , 51 , 52 , 53 …”
Section: Ecls As a Team Approachmentioning
confidence: 99%